2012
DOI: 10.2478/v10146-012-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids, ergosterol and tocopherols in fresh and preserved herbage and their transfer to bovine milk fat and adipose tissues: A review

Abstract: The requirements of cattle for the fat-soluble vitamins A, D and E, their provitamins and some carotenoids have increased under conditions of intensive husbandry with insufficient provision of fresh forage, their cheapest natural source. Moreover, bovine milk fat and adipose tissues participate in the intake of these micronutrients by humans. Four major carotenoids occurring in forage crops are lutein, all-trans-β-carotene, zeaxanthin and epilutein. Fresh forage is their richest source. Losses are significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 45 publications
4
23
0
1
Order By: Relevance
“…As it is can be seen in Table 2, the augmentative tendency of ERG content found in the fresh forage samples of orchardgrass from 2012 to 2013 was related at the higher rainy conditions in the second year, contributing to the occurrence and development of fungi. The ERG increase at high relative humidity and lower temperature was previously corroborated by Kalač [44]. In addition, the high ERG content is related to the delayed harvest date [27] and the higher frequency of rains [45] at the timing of harvest.…”
Section: Discussionsupporting
confidence: 54%
“…As it is can be seen in Table 2, the augmentative tendency of ERG content found in the fresh forage samples of orchardgrass from 2012 to 2013 was related at the higher rainy conditions in the second year, contributing to the occurrence and development of fungi. The ERG increase at high relative humidity and lower temperature was previously corroborated by Kalač [44]. In addition, the high ERG content is related to the delayed harvest date [27] and the higher frequency of rains [45] at the timing of harvest.…”
Section: Discussionsupporting
confidence: 54%
“…Information about tocopherol content in fresh forage is not consistent (Kalac 2012). Larsen et al (2012) reported that the concentrations of α-tocopherol in various grasses and legumes vary considerably with plant maturity and, to a lesser extent, with species.…”
Section: Discussionmentioning
confidence: 99%
“…In feed and in foods of plant origin, vitamin E is present in the form of eight chemical compounds, including four tocopherols (α, β, γ, δ) and four tocotrienols (α, β, γ, δ). Milk fat contains only α‐tocopherol which characteristically has the highest antioxidant activity (Akoh and Min ; Kalač ). According to Akoh and Min (), α‐tocopherol demonstrates 100% activity, whereas the biological activity of γ‐ and δ‐tocopherols is 10 and 100 times lower, respectively.…”
Section: Vitamin Ementioning
confidence: 99%